2019
DOI: 10.1177/0885066618824531
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Novel Biomarkers for the Diagnosis of Acute Kidney Injury: A Historical Perspective

Abstract: Acute kidney injury (AKI) is a common and serious medical condition associated with significant increases in morbidity, mortality, and cost of care. Because of the high incidence and poor outcomes associated with AKI, there has been significant interest in the development of new therapies for the prevention and treatment of the disease. A lack of efficacy in drug trials led to the concern that AKI was not being diagnosed early enough for an effective intervention and that a rise in serum creatinine itself is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 97 publications
(100 reference statements)
0
25
0
1
Order By: Relevance
“…In addition, several notable drug trial failures raised concerns that AKI was not diagnosed early enough for effective intervention and that a rise in serum creatinine itself is not a sensitive enough marker (Griffin et al, 2018). Biomarkers have been proven to be important tools for current and future AKI research and clinical management (Griffin et al, 2019). Novel biomarkers can not only enable assessment of declines in kidney function but also indicate structural damage in the kidneys at earlier time points than increases in serum creatinine.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several notable drug trial failures raised concerns that AKI was not diagnosed early enough for effective intervention and that a rise in serum creatinine itself is not a sensitive enough marker (Griffin et al, 2018). Biomarkers have been proven to be important tools for current and future AKI research and clinical management (Griffin et al, 2019). Novel biomarkers can not only enable assessment of declines in kidney function but also indicate structural damage in the kidneys at earlier time points than increases in serum creatinine.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of capturing abnormalities preceding the decrease in GFR, novel biomarkers of kidney injury have been developed showing a high sensitivity in detecting the early kidney damage in several conditions . Studies in humans mainly focused on the use of markers of kidney injury in different emergency settings, as critically ill patients, heart failure, after major cardiac surgery, kidney transplantation or cisplatin administration, and in the evaluation of contrast‐induced acute kidney injury . Elevation of many of the novel biomarkers has been described in animal and human studies of drug‐induced kidney toxicity [eg kidney injury molecule‐1 (KIM‐1), β2‐microglobulin (B2M), cystatin C, interleukin‐18 (IL‐18), neutrophil gelatinase‐associated lipocalin, (NGAL)] …”
Section: Introductionmentioning
confidence: 99%
“…Fewer data are reported in chronic disease . The overall data showed that the assessment of a panel of the novel biomarkers is useful in the early detection of kidney injury, with high prognostic value . As far as endocrine disease, recent works have shown that the assessment of biomarkers of tubular damage could have diagnostic value in screening patients for diabetic kidney disease .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations